Screens to solutions: the role of digital health communication in preventing chronic kidney disease in Ghana - Abdallah, Amina (My University, 2025)
This thesis investigates the role of digital health communication in shaping awareness, information-seeking behaviors, and preventive health actions related to chronic kidney disease (CKD) among Ghanaians. With the increasing use of digital platforms for health-related purposes, this study explores how digital media influence CKD knowledge and behavior in a population facing rising rates of chronic illness and limited early detection. Grounded in the Health Belief Model (HBM) (Rosenstock, 1974) and Technology Acceptance Model (TAM) (Davis, 1985), the research examines the effects of perceived susceptibility, severity, benefits, barriers, cues to action, self-efficacy, and technology acceptance (perceived ease of use and usefulness) on CKD-related behaviors. Additional variables include digital media use, gender differences, and cultural influences on health behavior. A quantitative approach was employed, with data collected through an online survey (n=298). The sample was composed of 128 men, 134 women, and 15 who preferred not to identify. Descriptive statistics were calculated, including percentages, means, and standard deviations. Correlation and regression analyses were conducted to test the hypotheses and answer the research questions. Findings show that perceived benefits ([beta] = .256, t = 2.77, p = .006) and cues to action were significant predictors of CKD knowledge and preventive behavior, while perceived susceptibility ([beta] = –.200, t = –3.24, p = .001) was negatively associated with knowledge. Perceived ease of use ([beta] = .211, t = 2.89, p = .004) and usefulness ([beta] = .202, t = 2.72, p = .007) of digital platforms significantly predicted CKD awareness, supporting TAM’s premise. Notably, gender differences were found in perceived barriers, with women reporting significantly more obstacles to preventive behavior (p = .002). Regression analyses revealed that health beliefs, digital platform acceptance, and subjective norms explained a significant proportion of variance in preventive and information-seeking behavior. These findings underscore the complex interplay between technological access, belief systems, and cultural context in health communication. This study highlights the potential of digital health communication to improve CKD awareness to promote preventive action in Ghana. It emphasizes the need for culturally relevant, user-friendly digital interventions that consider gender, literacy, and social support systems to effectively bridge gaps in health knowledge and behavior.
Keywords: Chronic kidney disease; Digital health communication; Health awareness; Ghana; Social media use